PENGARUH LITERASI EKOLOGI TERHADAP PERILAKU PEDULI LINGKUNGAN MTS SWASTA YPIP PANJENG - Neti Wulandari; Nela Nur Fadila; Sri Wahyuni; Sri Wulan Ika Pamuji Rahayu; Zayyana Nor Fadlilah; Rizki Ilham Maulana; Aristiawan Aristiawan (JURNAL TARBIYAH, 2024)
Environmental sustainability awareness is an evaluation for the provision of understanding and application from an early age through learning obtained from the environment. Education is a means of implementing ecological literacy in shaping behavior of concern for the environment, especially among students. Ecotourism learning is an alternative to promoting ecological literacy to apply environmental care. This study aims to measure the influence of ecological literacy based on ecotourism learning on the behavior of environmental care students in grade VII at YPIP Panjeng Private MTs. Proportionally, quantitative research was conducted on 100 students of SMP MTs YPIP Panjeng with causal sociation. This research emphasizes the importance of ecological literacy in increasing students' environmental awareness, with recommendations for the integration of ecological materials in the curriculum and practical activities in schools. Ecotourism learning on ecological literacy has a positive effect on environmental care behavior, with a regression coefficient of 0.546. Every 1% increase in ecotourism-based ecological literacy increases environmental care behavior by 0.546. The increase in students' environmental care behavior at 10.3% was due to students' ecological literacy, while 89.7% was explained by other supporting factors.